2015
DOI: 10.7322/abcshs.v40i1.698
|View full text |Cite
|
Sign up to set email alerts
|

O benefício da dança sênior em relação ao equilíbrio e às atividades de vida diárias no idoso

Abstract: introdução: Com a chegada da velhice, ocorrem mudanças que determinam uma progressiva perda da capacidade de adaptação do indivíduo, resultando em dificuldades para manter o equilíbrio ao realizar suas atividades de vida diárias, dificultando a convivência na sociedade. A dança, por sua vez, proporciona a melhora da capacidade funcional e dos benefícios psicológicos. objetivo: Avaliar o benefício da dança sênior em relação ao equilíbrio e às atividades de vida diárias no idoso. métodos: Participaram do grupo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 16 publications
0
11
0
18
Order By: Relevance
“…The participation in the senior dance group also enables the autonomy because it stimulates the older adult to leave the house and socialize, participate and make decisions in the community where she/he lives, for the sake of health and well-being. In a study conducted by a senior dance group in São Paulo (20) , whose goal was to evaluate the benefit of dance for 25 participants, the authors concluded that dancing brings benefits to balance, assists in activities of daily life, and stimulates autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…The participation in the senior dance group also enables the autonomy because it stimulates the older adult to leave the house and socialize, participate and make decisions in the community where she/he lives, for the sake of health and well-being. In a study conducted by a senior dance group in São Paulo (20) , whose goal was to evaluate the benefit of dance for 25 participants, the authors concluded that dancing brings benefits to balance, assists in activities of daily life, and stimulates autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Senior Dance is becoming increasingly popular among the older population in Brazil 37. Senior Dance classes consist of different choreographies, which include rhythmic and simple movements with rhythmic folk songs.…”
Section: Introductionmentioning
confidence: 99%
“…A base de dados que resgatou o maior número de publicações foi a CINAHL, 41,90% (31), seguida da LILACS, com 20,28% (15), e SCOPUS, com 17,56% (13). Em relação ao idioma, verifica-se a predominância de publicações no idioma inglês, com 77,02% (57), seguido do idioma português, com 22,98% (17).…”
Section: Resultsunclassified
“…Dados de estudo, desenvolvido em São Paulo com 19 idosos, que objetivou avaliar o benefício da dança sênior em relação ao equilíbrio e atividades de vida diária no idoso, reforçam os achados encontrados na revisão, uma vez que, a partir dos resultados desse estudo, foi possível identificar que a prática de dança sênior trouxe melhora do equilíbrio e das atividades de vida diárias. Considerando que o equilíbrio e o risco de queda foram avaliados pela escala de Berg e a independência nas atividades de vida diárias avaliadas pela escala de Lawton (17) .…”
Section: Discussionunclassified